PERANCANGAN TATA LETAK FASILITAS PRODUKSI KAPAL DI PABRIK TAPOS PT SIB DENGAN PERTIMBANGAN LUAS DAN ORIENTASI DEPARTEMEN - Ghazi Ichsan, Achmad
Pabrik Tapos PT SIB is one of PT SIB’s facilities that manufactures medium-sized ships. The Production Division of Pabrik Tapos PT SIB is needed to create different facility layouts for different production batches. The facility layout evaluation for the production batch in January – June 2024 production period shows a high material handling cost valued at 28846.15r where r is a particular rupiah value. One of the causes is the nonoptimal production facility layout. By that, this research will focus on designing a ship production facility layout for the next production batch at Pabrik Tapos PT SIB that minimizes the material handling cost. A representative mathematical model is needed to describe the facility layout problem. Adjusted to the ship production facility layout at Pabrik Tapos PT SIB, the model must accommodate the change of departments’ orientation with fixed and unequal areas. This research will use the heuristic algorithm to solve the model because there are many departments to be considered. By considering adjustments and model complexity, this research will represent the layout problem using a mixed-integer linear programming (MILP) mathematical model and find its solutions using the combination of zone algorithm (ZA), modified median method (3M), group movement (GM), and modified 2-Opt algorithm. Layouts are generated using the combined algorithm with computer programming. After the results are verified, the combined algorithm can generate 24 feasible layout alternatives that match the mathematical model from 33 generated layouts. The best layout shows an 11.65% reduction in material handling cost compared to the last production’s facility layout.